A scoring system for AML patients aged 70 years or older, eligible for intensive chemotherapy: a study based on a large European data set using the DATAML, SAL, and PETHEMA registries - Bérard, Emilie; Röllig, Christoph; Bertoli, Sarah; Pigneux, Arnaud; Tavitian, Suzanne; Kramer, Michael; Serve, Hubert; Bornhäuser, Martin; Platzbecker, Uwe; Müller-Tidow, Carsten; Baldus, Claudia D.; Martínez-Cuadrón, David; et al. (Blood cancer journal, 2022)
In a context of therapeutic revolution in older adults with AML, it is becoming increasingly important to select patients for the various treatment options by taking account of short-term efficacy and toxicity as well as long-term survival. Here, the data from three European registries for 1,199 AML patients aged 70 years or older treated with intensive chemotherapy were used to develop a prognostic scoring system. The median follow-up was 50.8 months. In the training set of 636 patients, age, performance status, secondary AML, leukocytosis, and cytogenetics, as well as NPM1 mutations (without FLT3-ITD), were all significantly associated with overall survival, albeit not to the same degree. These factors were used to develop a score that predicts long-term overall survival. Three risk-groups were identified: a lower, intermediate and higher-risk score with predicted 5-year overall survival (OS) probabilities of ≥12% (n = 283, 51%; median OS = 18 months), 3-12% (n = 226, 41%; median OS = 9 months) and <3% (n = 47, 8%; median OS = 3 months), respectively. This scoring system was also significantly associated with complete remission, early death and relapse-free survival; performed similarly in the external validation cohort (n = 563) and showed a lower false-positive rate than previously published scores. The European Scoring System ≥70, easy for routine calculation, predicts long-term survival in older AML patients considered for intensive chemotherapy.